Comparison of the Efficacy of Disinfectant Pre-impregnated Wipes for Decontaminating Stainless Steel Carriers Experimentally Inoculated With Ebola Virus and Vesicular Stomatitis Virus - Cutts, Todd A.; Kasloff, Samantha B.; Krishnan, Jay; Nims, Raymond W.; Theriault, Steven S.; Rubino, Joseph R.; Ijaz, M. Khalid (Frontiers in Public Health, 2021)
The authors evaluated four disinfectant pre-impregnated wipes (DPW) for efficacy against Ebola virus Makona variant (EBOV) and vesicular stomatitis virus (VSV), Indiana serotype. Steel carriers were inoculated with the infectious virus and then were wiped with DPW in the Wiperator instrument per ASTM E2967-15. Following the use of J-Cloth impregnated with medium (negative control wipes) or the use of activated hydrogen peroxide (AHP)-, ethanol-, sodium hypochlorite (NaOCl)-, or single or dual quaternary ammonium compound (QAC)-based DPW, virus recovery from the carriers was assayed by titration assay and by two passages on Vero E6 cells in 6-well plates. The Wiperator also enabled the measurement of potential transfer of the virus from the inoculated carrier to a secondary carrier by the DPW or control wipes. The J-Cloth wipes wetted with medium alone (no microbicidal active) removed 1.9–3.5 log10 of virus from inoculated carriers but transferred 4 log10 of the wiped virus to secondary carriers. DPW containing AHP, ethanol, NaOCl, or single or dual QAC as active microbicidal ingredients removed/inactivated 6 log10 of the virus, with minimal EBOV or no VSV virus transfer to a secondary surface observed. In Ebola virus outbreaks, a DPW with demonstrated virucidal efficacy, used as directed, may help to mitigate the unintended spread of the infectious virus while performing surface cleaning.